IMPLEMENTASI LOGIKA FUZZY MAMDANI PADA SISTEM REKOMENDASI PERPANJANGAN KONTRAK KERJA KARYAWAN - dwi marisa efendi (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2019)
Distributor companies in carrying out activities require better employees. In determining the good employees, often meet obstacles, usually the assessment is still objective, especially in terms of contract extension. In accordance with these needs the writer will create a system that can determine the extension of the contract to be more objective and accurate. In planning the system, he development method used is the waterfall method and the development tools used are flowcharts, data flow diagrams and the method used for prediction is to use the fuzzy method, the writer chose fuzzy mamdani to help solve predictions in this system. The fuzzy mamdani method uses several criteria or variables including Absence, Achievement, Long Work, Cooperation, Graduates, Age. For the application of the application system supporting the decision of a contract extension is Microsoft Visual Basic 6.0. The final results of this study are employees whose work contracts are extended by a value of 1.7. Imron Rusdi 1.5. Arif Hamdani 1.5. Suanda 4. Risman 2. Wardoyo 2..